Moderate Islamic Character Education as a Preventive Strategy Against Religious Extremism: A Case Study - Mizlan, Mizlan; Achadi, Muh Wasith (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2026)
Religious extremism poses a serious challenge to social stability and education in Indonesia, including in the Bangka Belitung region, which is characterized by cultural and religious diversity. This study aims to analyze the implementation of moderate Islamic character education at SMK Negeri 2 Pangkalpinang and its effectiveness as a strategy to prevent radicalization in vocational school environments. The study employs a qualitative approach with a case study design. Data were collected through in-depth interviews with the school principal, Islamic education teachers, guidance counselors, student council members, and students, supported by participatory observation and documentary studies. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana, which includes data reduction, data presentation, and drawing conclusions through triangulation of sources and techniques. The results of the study indicate that moderate Islamic character education is integrated into the PAI curriculum, extracurricular activities, and character-building programs based on the values of tawasuth, tasamuh, and tawazun. The internalization of these values is evident in students' attitudes of tolerance, social empathy, and rejection of radical content on social media. Additionally, collaboration between schools and the Ministry of Religion, police, and civil society organizations strengthens students' digital literacy and national awareness. These findings confirm that moderate Islamic education functions as a soft approach in the Countering Violent Extremism (CVE) strategy, especially in vocational schools that are vulnerable to radical ideology infiltration. The implications of this study contribute theoretically to the development of a model of religious moderation education and practically to national education policies oriented toward strengthening the moderate character of the younger generation.